El e-Alter Ego:Fantasmas en Internet - Rojas Galeano, Sergio Andrés (Ingeniería, 2000)
Internet metamorphosis in the last four years has been astonishing. From just a data reservoir used for e-mail and web pages publishing, it becomes into a virtual social space for: goods, service and knowledge interchange; emotional, labor and fraternity relationships development; behavior and business models invention; and sharing worlds information resources. Hence it is a new digital world there must been software entities living inside, acting in our beliefs and purposes. These electronic alter ego would be responsible for the next Internet revolution, and would have a great impact in our way-of-life.This paper reviews this issue and discusses about its importance and perspectives.